HYPERBOLIC EXPRESSIONS AS REVEALING SENSE OF DEPRESSION IN RADIOHEAD’S “OK COMPUTER” ALBUM - Ramawijaya, Teguh; Sunra, La; Affandi, Akhmad (Journal of English Literature and Linguistic Studies, 2025)
This study explores how hyperbolic expressions in the lyrics of Radiohead’s OK Computer represent depression and influence listeners' perceptions of mental health. Using psychological theories from Edward Bibring and Sigmund Freud, alongside Hans Georg Gadamer’s hermeneutic approach, the research examines how exaggerated phrases intensify themes of overwhelming mental struggle, invasive thoughts, despair, and alienation. These hyperbolic expressions vividly portray the emotional chaos and isolation of depression, making it more relatable for listeners. The findings show that these expressions evoke strong emotional responses, deepening empathy and shaping listeners' understanding of depression. This study highlights the role of music in influencing public perceptions of mental health.